2005
DOI: 10.1111/j.1440-169x.2005.00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an exchangeable gene trap using pU‐17 carrying a stop codon‐βgeo cassette

Abstract: We have developed a new exchangeable gene trap vector, pU-17, carrying the intron-lox71-splicing acceptor (SA)-βgeo-loxP-pA-lox2272-pSP73-lox511. The SA contains three stop codons in-frame with the ATG of βgalactosidase/neomycin-resistance fusion gene (βgeo) that can function in promoter trapping. We found that the trap vector was highly selective for integrations in the introns adjacent to the exon containing the start codon. Furthermore, by using the Cre-mutant lox system, we successfully replaced the βgeo g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 38 publications
(56 reference statements)
0
63
0
Order By: Relevance
“…From this point of view, iPLA 2 ␥ may be responsible for the repair of peroxidized CL in mitochondria. It has been proposed that the consecutive action of PLA 2 and glutathione peroxidase (GPx) is required to reduce lipid peroxides in mitochondria ( 24 ). Like the gene disruption of iPLA 2 ␥ observed in the present study, gene disruption of cGPx, one of the GPx isozymes, has also been shown to result in growth retardation, presumably due in part to mitochondria disorders ( 58 ).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…From this point of view, iPLA 2 ␥ may be responsible for the repair of peroxidized CL in mitochondria. It has been proposed that the consecutive action of PLA 2 and glutathione peroxidase (GPx) is required to reduce lipid peroxides in mitochondria ( 24 ). Like the gene disruption of iPLA 2 ␥ observed in the present study, gene disruption of cGPx, one of the GPx isozymes, has also been shown to result in growth retardation, presumably due in part to mitochondria disorders ( 58 ).…”
Section: Discussionmentioning
confidence: 48%
“…The iPLA 2 ␥ gene was disrupted by gene-trapping methods ( 24 ), in which a gene cassette consisting of a splicing acceptor (SA)-␤ geo-pA-pSP73 was integrated between exons 1 and 2 (supplementary Fig. IA).…”
Section: Methodsmentioning
confidence: 99%
“…A BLAST search using the mouse cDNA sequence identified line Ayu21-18 (15). The description of the generation of Ayu21-18 can be found at http://egtc.jp.…”
Section: Ayu21-18 An Es Cell Line With a Gene-trap Insertion In The mentioning
confidence: 99%
“…) by gene-trap insertional mutagenesis in embryonic stem cells using an exchangeable trap vector (Taniwaki et al, 2005). Our mutant mice exhibit a milder phenotype than the null mutant mice in terms of their growth and perinatal death rate.…”
Section: Gt/gtmentioning
confidence: 99%